2016
DOI: 10.3855/jidc.7656
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular analysis on the relationships between type 2 diabetes mellitus and hepatitis B virus infection

Abstract: Introduction: This study aimed to further analyze the associations between type 2 diabetes mellitus (T2DM) and hepatitis B virus (HBV) infection, and to investigate the relationships between T2DM and the mutations within the HBV major hydrophilic region (MHR). Methodology: In this cross-sectional study, 3,377 persons (338 T2DM patients and 3,039 non-diabetics) were randomly selected. HBsAg detection was performed by enzyme-linked immunosorbent assay. The HBV MHR was amplified, sequenced, and analyzed by nested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In our recent studies, we first reported that the amino acid substitution rates in the "a" determinant were significantly higher in the patients with type 2 diabetes mellitus, as compared with non-diabetic individuals. 32 Additionally, our another studies observed that vitamin D deficiency was significantly associated with the mutation frequency of M133 in HBV infected patients, indicating that the obesity might lead to an increased risk of HBV vaccine-escape mutations. 33 …”
Section: Discussionmentioning
confidence: 89%
“…In our recent studies, we first reported that the amino acid substitution rates in the "a" determinant were significantly higher in the patients with type 2 diabetes mellitus, as compared with non-diabetic individuals. 32 Additionally, our another studies observed that vitamin D deficiency was significantly associated with the mutation frequency of M133 in HBV infected patients, indicating that the obesity might lead to an increased risk of HBV vaccine-escape mutations. 33 …”
Section: Discussionmentioning
confidence: 89%
“…An increased risk of infection and poorer outcomes in type 2 diabetes (T2D) is seen for intracellular pathogens, with a threefold increased risk of developing tuberculosis (TB) , and increased risk of death or treatment failure in TB . Relationships between diabetes and a range of global pathogens have been reported, including Hepatitis B , Hepatitis C , and dengue . Defects in activation and function of innate immune cells, and a subsequent delay of IFN‐γ driven T cell responses have been implicated in the increased susceptibility to infection .…”
Section: Introductionmentioning
confidence: 99%
“…Due to multiple factors, such as suppression of immune defense, microangiopathy, and the hyperglycemic environment, patients with DM are more vulnerable to infection and tend to experience increased mortality from infectious diseases (Korbel et al, 2018;Zoppini et al, 2018). It has been suggested that hepatitis B/C virus and tuberculosis infections are more prevalent in diabetic patients (Ba-Essa et al, 2016;Ronacher et al, 2015;Zhu et al, 2016). Furthermore, increasing reports indicate that there is an association between type 2 diabetes mellitus (DM-2) and KSHV infection or the development of KS (Caselli et al, 2014;Ingianni et al, 2007;Sobngwi et al, 2008), while the evidence is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Low-and middleincome countries assume almost 80% of the diabetes burden (International Diabetes Federation, 2017). DM-2, characterized by insulin resistance and hyperglycemia, is the most prevalent metabolic disorder in China (Zhu et al, 2016). There is an urgent need to improve the prognosis of diabetic patients and reduce the global burden of this chronic disease.…”
Section: Introductionmentioning
confidence: 99%